(untitled) - Gottlieb, Steven (Lanham, 2011)
These photographs provide an interpretation of our nation's capital that is both stirring and joyful, reverent yet luminous.
Keywords: World war, 1939-1945,Chiến tranh thế giới, 1939-1945; Washington (D.C.); Washington (D.C.)